Escape From Egypt - Booth, Bradley; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 2009)
Fourteen-year old Meshack, a Levite, grows in faith and trust in Jehovah while serving as a messenger for Aaron and Moses as the Israelite s leave the slavery of Egypt to cross the desert and make their way to Canaan.
Keywords: Young Adult